Landscape of Monoclonal Antibodies Targeting Zika and Dengue: Therapeutic Solutions and Critical Insights for Vaccine Development - Dussupt, Vincent; Modjarrad, Kayvon; Krebs, Shelly J. (Frontiers in Immunology, 2021)
The unprecedented 2015-2016 Zika outbreak in the Americas sparked global concern and drove the rapid deployment of vaccine and therapeutic countermeasures against this re-emerging pathogen. Alongside vaccine development, a number of potent neutralizing antibodies against Zika and related flaviviruses have been identified in recent years. High-throughput antibody isolation approaches have contributed to a better understanding of the B cell responses elicited following infection and/or vaccination. Structure-based approaches have illuminated species-specific and cross-protective epitopes of therapeutic value. This review will highlight previously described monoclonal antibodies with the best therapeutic potential against ZIKV and dengue, and discuss their implications for the rational design of better vaccine strategies.